Conformities to law of forming of corporate mechanism of material stimulation of workers of machine-building enterprises - Victoria Pavlovska (Cхід, 2013)
Essence, conformities to law of forming and component ingredients of corporate mechanism of material stimulation of workers, is found out in the article. Essence and features of organization of ecology-economical activity of workers are exposed. Essence of stimulation of ecology-economical activity of workers is certain. Methodical approaches are marked in relation to providing of functionality of corporate mechanism of material stimulation of ecology-economical activity of workers of enterprises of engineer.